Power flow and power quality improvement of a residential-industrial microgrid using 72-pulse inverter-based UIPC - Mahyar Abasi; Ali Nahavandi; Javad Ebrahimi; Gevork B. Gharehpetian (International Journal of Electrical Power & Energy Systems)
This article offers a design of simultaneous reactive-active power control, total harmonic distortion reduction, and voltage unbalance compensation at the connection point of an industrial-residential microgrid, containing an electric arc furnace and a wind farm, to a power system. As large reactive power consumers, arc furnaces have a completely nonlinear and unbalanced behavior that directly affects power quality indices and reactive power control. On the other hand, the presence of wind farms in the microgrid poses challenges in accurately controlling reactive and active power, transient stability, and low-voltage ride-through capability. Further, the combination of the two increases short-circuit capacity and ultimately creates protective issues during faults. Accordingly, this article presents a plan to use a unified inter-phase controller at the connection point of the microgrid to the main grid to tackle the challenges. Two contributions are considered in the structure of the control system and the switching algorithm of the proposed converter. The first is related to the control system design based on the dq0 and proportional-integral controller, which is capable of producing the required signals of a 72-pulse voltage source converter. The second contribution is related to presenting a switching pattern to produce the 72-pulse voltage signals, represented in this article with an explicit mathematical function. The control design is capable of controlling the active and reactive power of the microgrid in various conditions of normal and critical performance. It also improves the microgrid power quality and the connected power system. The design presented in this work was modeled and implemented in MATLAB software, and the results of different test scenarios validated the optimal performance of the suggested design.